ANALISIS BERPIKIR KRITIS PESERTA DIDIK KELAS VIII DITINJAU DARI GENDER DI MTs ASSHOLACH GONDANGWETAN PASURUAN - Faiqoh (Universitas Nahdlatul Ulama Pasuruan, 2023)
This research was conducted to find out and describe how class VIII students of ASSHOLACH MTs think critically based on gender differences, to know and describe the supporting factors and inhibiting factors for students of class VIII MTs ASSHOLACH to think critically. This study uses a qualitative method with a type of field research. The subjects in this study were class VIII assholach madrasah tsanawiyah students. Critical thinking analysis in research refers to the FOCUS criteria, namely Focus, Reason, Inference, Clarity and Overview proposed by Ennis. Data collection techniques, namely test techniques, interviews, observation, and documentation. The results of this study were that the subject of male students fulfilled the five critical thinking criteria namely Focus, Reason, Inference, Situation, Clarity, while the overview criteria were not met. Whereas on the subject of female students fulfilling all the criteria for critical thinking, namely Focus, Reason, Inference, Situation, Clarity and Overview. Based on the results of this study, the researchers concluded that female students were better than male students in terms of critical thinking skills because male students did a thorough re-check, namely on the overview indicator and there were differences in the process.s.